BIOFILM ERADICATION ACTIVITY OF PARTIALLY PURIFIED FRACTION OF ETHYLACETATE EXTRACT OF ACALYPHA WILKESIANA LEAVES ON CANDIDA ALBICANS I, II AND PARAPSILOSIS (FUDMA JOURNAL OF SCIENCES, 2021)
Candida spp produce highly structured biofilms composed of multiple cells encased in an extracellular matrix. Sessile cells are known to decrease drug diffusion toward biological targets. This research is aimed at evaluating the biofilm eradication activity of partially purified fraction of ethylacetate extract of Acalypha wilkesiana leaves on sessile cells of C. albicans I, II and C. parapsilosis. Column Chromatography-TLC was used to fractionate and partially purify the extract using a bioassay guided fractionation. Preparative TLC was used to purify the most potent fraction. Antifungal effects of the extract and percentage biofilm eradication was determined by microdilution method. Antibiofilm activity of the purified fraction on the morphology of the sessile cells of Candida spp was evaluated by scanning electron microscopy. The purified fraction had MIC of 1.25mg/ml on C. albicans I, II and C. parapsilosis, respectively.  MFC of 2.5mg/ml on C. albicans I and II but there was no total death observed on C. parapsilosis. The fraction had IC50 significantly (p â‰¤ 0.05) different from that of the reference drugs. There was significant (p â‰¤ 0.05) increase in the biofilm eradicated by corilagin, amp B., voriconazole, caspafungin, compared to the purified fraction on C. albicans I, II and C. parapsilosis. There was decrease in biomass of sessile cells on the morphology of C. albicans I, II and C. parapsilosis in all treated plates compared to the control. Therefore, the purified fraction of ethylacetate extract of A. wilkesiana leaves has a potential to eradicate the biofilms formed by Candida spp.
Keywords: Acalypha wilkesiana, Microdilution, Scanning Electron Microscopy, Extracellular Matrix